2006
DOI: 10.1007/s00431-005-0048-1
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of hyponatremic-hypertensive syndrome in childhood with renovascular hypertension

Abstract: Both patients showed rapidly progressive renovascular hypertension and loss of function of the affected kidney. In order to preserve renal function in such cases, early invasive intervention appears to be necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…In our study, two patients presented with hyponatremic hypertensive syndrome, which is rare in children [2,23]. Therefore, while electrolyte disturbances must be screened to exclude other causes of hypertension such as monogenic etiologies, they are not a sensitive marker for the diagnosis of renovascular hypertension.…”
Section: Discussionmentioning
confidence: 94%
“…In our study, two patients presented with hyponatremic hypertensive syndrome, which is rare in children [2,23]. Therefore, while electrolyte disturbances must be screened to exclude other causes of hypertension such as monogenic etiologies, they are not a sensitive marker for the diagnosis of renovascular hypertension.…”
Section: Discussionmentioning
confidence: 94%
“…Although initially considered a rare condition, HHS has been identified in approximately 16% of adults with unilateral renal artery stenosis [4,10]. Data on the pediatric population are still sparse [5][6][7][8][9][10][11]. In an editorial commentary, Nicholls [2] suggested that HHS may be underdiagnosed in children and probably more common than previously thought.…”
Section: Discussionmentioning
confidence: 95%
“…All of these changes, along with the sodium depletion secondary to pressure natriuresis, cause hyponatremia. The pressure-induced hyperfiltration and natriuresis might be responsible for the hypercalciuria and hyperuricosuria, while the proteinuria may be secondary to hyperfiltration due to the proteinuric effect of angiotensin II and, probably, atrial natriuretic peptide [2,9,10,[13][14][15]. Accordingly, for HHS to occur, the stenosis of the renal artery must be unilateral, and perfusion and function of the contralateral kidney must be normal [9,13].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations